2014
DOI: 10.4244/eijv10i4a77
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography study of healing characteristics of paclitaxel-eluting balloons vs. everolimus-eluting stents for in-stent restenosis: the SEDUCE (Safety and Efficacy of a Drug elUting balloon in Coronary artery rEstenosis) randomised clinical trial

Abstract: http://www.clinicaltrials.gov. Unique identifier: NCT 01065532.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…In the mechanistic SEDUCE (Healing Responses After Treatment of Bare Metal Stent Restenosis With Implantation of an Everolimus-Eluting Xience V Stent Versus Use of a Paclitaxel-Eluting Balloon: Optical Coherence Tomography Study) randomized trial, 29 optical coherence tomography was used to assess the healing characteristics of patients with BMS-ISR allocated to EES or DEB (25 patients per arm). DEB were associated with better healing characteristics (strut coverage on optical 16 demonstrating that EES improved all late angiographic parameters.…”
Section: Alfonso Et Al Everolimus-eluting Stents For In-stent Restenosismentioning
confidence: 99%
“…In the mechanistic SEDUCE (Healing Responses After Treatment of Bare Metal Stent Restenosis With Implantation of an Everolimus-Eluting Xience V Stent Versus Use of a Paclitaxel-Eluting Balloon: Optical Coherence Tomography Study) randomized trial, 29 optical coherence tomography was used to assess the healing characteristics of patients with BMS-ISR allocated to EES or DEB (25 patients per arm). DEB were associated with better healing characteristics (strut coverage on optical 16 demonstrating that EES improved all late angiographic parameters.…”
Section: Alfonso Et Al Everolimus-eluting Stents For In-stent Restenosismentioning
confidence: 99%
“…Its efficacy against other treatment strategies has been demonstrated in both randomised controlled trials [9] and in the real world setting [10]. Comparisons to date however have predominantly been between DEB, POBA and first generation DES [9], and individual studies comparing DEB to second generation DES have been relatively small in scale [11][12][13][14][15][16][17]. Herein we present the findings of our meta-analysis examining the efficacy of DEB in the treatment of ISR specifically in comparison to second generation DES.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 2,173 patients are included in this analysis (31.4% from RCTs), 1,167 treated with a DES, and 1,006 treated with DCB. The sample size of the individual studies ranged from 50 to 628 patients . Three studies reported results on patients presenting with BMS‐ISR, four on patients with DES‐ISR and three other studies included a combined BMS/DES ISR population.…”
Section: Resultsmentioning
confidence: 99%
“…Last, one study that reported outcomes on patients treated with a sirolimus-eluting newer generation stent, was excluded because the scope of this meta-analysis was to compare DCB versus stents with the newer-limus substances (everolimus, zotarolimus, and biolimus). Ultimately, 10 studies were included in this systematic review and meta-analysis [20,21,24,25,[33][34][35][36][37][38]. The PRISMA Flow Diagram presents the selection of studies in Figure 1.…”
Section: R E Su Ltsmentioning
confidence: 99%